Der Kampf um die Autokephalie der georgisch-orthodoxen Kirche als Bindeglied zwischen Klerus und Nationalbewegung (1860-1918) - Reisner, Öliver (Georgica, 2017)
The issue of the sacralization of the nation and the nationalisation of religion is a direct consequence of the tsarist clerical and colonial policy in Georgia. The emerging secular national movement altered the views of a segment of the clergy and influenced transformations within agrarian society at the turn of the 19th and 20th centuries. The paper initially explores the role and function of the Georgian Church under the conditions of the country’s annexation by Russia; it helps to illustrate better the impact of tsarist ecclesiastical policy on the non-Slavic societies residing in the southern provinces of the empire. The subsequent part of the paper briefly characterises the perspectives of the nationally-minded intelligentsia regarding the church. The discussion focuses on Georgia’s autocephaly, which gained particular significance following the Revolution of 1905. In my 2004 doctoral dissertation, I attempted to compile a collective biography of the Georgian national movement, using the Society for the Spreading of Literacy Among Georgians as a case study. The number of members in this society reached 4,700 between 1879 and 1916. Among the 1,500 members about whom we know more than just a first and last name, 201 are clergymen. The number of clergy joining this society grew particularly rapidly and disproportionately at the beginning of the 20th century. This fact clearly demonstrates the readiness of the Orthodox Church at the time to integrate itself into the secular national movement. This rapprochement received widespread coverage in the contemporary press. The present paper aims to clarify certain issues related to this rapprochement.